Highly stereoselective construction of tetrahydroquinolines via cascade aza-Michael-Michael reaction: Formal [4+2] cycloaddition of β, γ-unsaturated α-ketoesters with 2-aminochalcones. Issue 50 (13th December 2018) - Duan, Cong; Yao, Yongqi; Ye, Ling; Shi, Zhichuan; Zhao, Zhigang; Li, Xuefeng
Abstract: An efficient cascade aza-Michael-Michael sequence for the preparation of tetrahydroquinolines has been established. Three contiguous stereogenic centers are created with high levels of enantioselectivities (79–99% ee) and exclusive diastereoselectivities in the presence of a bifunctional squaramide. This approach is compatible with a broad range of β, γ-unsaturated α-ketoesters and 2-aminochalcones. Our protocol indicated that β-site of β, γ-unsaturated α-ketoester is an available pro-nucleophilic site. Graphical abstract: